IMPLEMENTASI E LEARNING PADA PELAJARAN PAI DALAM PEMBENTUKAN EQ PESERTA DIDIK - Amatul Jadidah; Muhammad Hasyim (Jurnal Studi Pesantren, 2022)
Islamic education means an education system that is able to give a person the ability to lead his life in line with his ideals as well as various Islamic values that have imbued and adorned his personality. The term Islamic education is an educational system that includes all aspects of life that are needed by the servants of Allah, both worldly and in the hereafter.Islamic education has the goal of forming a personality as a caliph of Allah SWT or at least preparing for steps that refer to the final goal. The intended purpose is developed and realized on the basis of three elements of human nature, namely: 1. body, 2. spirit and 3. mind, each of which must be maintained. Various emotions can arise in oneself such as sadness, disappointment, hate, anger, joy, love. The name given to these emotions will affect how children think and act about these feelings. Therefore, it is necessary to implement Islamic education in shaping EQ (emotional Quantum). Success will be obtained if science, especially Islamic religious education, has been obtained at school, and in everyday life using electronic devices for positive activities, especially for religious knowledge, such as watching YouTube, Zoom, meetings, etc. which is called E learning.E-Learning is a learning activity that utilizes electronic devices that have a connection to the internet as a medium for delivering lessons to students. The electronic device can be in the form of a computer or smartphone positive things that are obtained are stored in the mind and remembered, shaped and applied, trained to keep them in mind and become knowledge in their minds, then a success is formed that can be obtained. in him. Keywords: Islamic Education, e-Learning, EQ